Detection of Norovirus in stool samples by RT-PCR from under five years age children hospitalized for acute gastroenteritis in Basrah, Iraq - Thwiny , Hazim (University of Thi-Qar Journal of Science, 2015)
Human noroviruses are the leading cause of non-bacterial gastroenteritis in children worldwide. The objectives of this study are to determine the frequency and importance of norovirus in diarrheal illness among children below 5 years of age and to investigate the most affected age, seasonal distribution and the major clinical symptoms associated with norovirus infections; 400 stool samples (200 symptomatic cases and 200 asymptomatic healthy children) were investigated during the period from March 2011 to March 2012.Norovirus was detected in 8% of symptomatic children whereas all the control groups were norovirus negative. Norovirus was highly prevalent among children of 18-23 months of age (P=0.05). Noroviruses were continuously detected throughout the year except in May and October, but the principle peaks of detection were in November. The most common clinical symptoms beside diarrhea observed among norovirus infected children were vomiting (94%), fever (69%), dehydration (50%) and abdominal pain found in 31%.